Pengaruh Penghindaran Pajak Terhadap Pengungkapan ESG Pada Perusahaan Manufaktur Subsektor Bahan Baku Di BEI - Alga Likita Paramartha; Intan Kurnia Permatasari (MEASUREMENT : Jurnal Program Studi Akuntansi, 2026)
This study aims to analyze the effect of tax avoidance on Environmental, Social, and Governance (ESG) disclosure in basic materials manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Tax avoidance is measured using Book–Tax Differences (BTD) as a proxy, while ESG disclosure is measured using a secondary ESG score based on GRI Standards from the ESGI database. Firm size is included as a control variable. This study employs a causal-associative quantitative approach with multiple linear regression analysis on 14 sample companies comprising 70 observations. The results indicate that tax avoidance has a positive and significant effect on ESG disclosure (regression coefficient 161.116; sig. 0.000), suggesting that companies respond to tax avoidance practices by increasing sustainability disclosure as a legitimacy strategy. Firm size has a negative and significant effect on ESG disclosure, indicating that larger companies in this subsector tend to be more selective in their disclosures. These findings are consistent with legitimacy theory, agency theory, and stakeholder theory.